Infection Prevalence at a Tertiary Hospital in Hail, Saudi Arabia: A Single-Center Study to Identify Strategies to Improve Antibiotic Usage - Alanazi M; Alqahtani HM; Alshammari MK; Alshammari RM; Malik JA; Ahmed S; Aroosa M; Shinde M; Alharby TN; Ansari M; Hussain A; Alkhrshawy FF; et al. (Infection and Drug Resistance, 2023)
Muteb Alanazi,1 Hassan Mohammed Alqahtani,1 Mohammad Khalid Alshammari,1 Raad Mohammed Alshammari,1 Jonaid Ahmad Malik,2,3 Sakeel Ahmed,4 Mir Aroosa,5 Mrunal Shinde,6 Tareq Nafea Alharby,1 Mukhtar Ansari,1 Arshad Hussain,1 Fahad F Alkhrshawy,7 Sirajudheen Anwar8 1Department of Clinical Pharmacy, College of Pharmacy, University of Hail, Hail, Saudi Arabia; 2Department of Pharmacology and Toxicology, National Institute of Pharmaceutical Education and Research, Guwahati, India; 3Department of Biomedical Engineering, Indian Institute of Technology Ropar, Rupnagar, India; 4Department of Pharmacology and Toxicology, National Institute of Pharmaceutical Education and Research, Ahmedabad, India; 5Department of Pharmacology and Toxicology, Jamia Hamdard, New Delhi, India; 6Department of Pharmaceutical Analysis, National Institute of Pharmaceutical Education and Research, Guwahati, India; 7Pharmaceutical Care Department, Hail General Hospital - Hail Health Cluster, Hail, Saudi Arabia; 8Department of Pharmacology and Toxicology, College of Pharmacy, University of Hail, Hail, Saudi ArabiaCorrespondence: Sirajudheen Anwar, Email si.anwar@uoh.edu.saObjective: Identifying the burden of disease and the condition of the Saudi population is in high demand from both a surveillance and analytical standpoint. The objective of this study was to determine the most prevalent infections among hospitalized patients (both community-acquired and hospital-acquired), the antibiotics prescribing pattern, and their relationship with patient characteristics like age and gender.Methods: A retrospective study was conducted comprising 2646 patients with infectious diseases or complications admitted to a tertiary hospital in the Hail region of Saudi Arabia. A standardized form was used to collect information from patient’s medical records. Demographic data such as age, gender, prescribed antibiotics, and culture-sensitivity tests were included in the study.Results: Males represented about two-thirds (66.5%, n = 1760) of the patients. Most patients (45.9%) who suffered from infectious diseases were between the ages of 20 and 39. The most prevalent infectious ailment was respiratory tract infection (17.65%, n = 467). Furthermore, the most common multiple infectious diseases were gallbladder calculi with cholecystitis (40.3%, n = 69). Similarly, COVID-19 had the greatest impact on people over 60. Beta-lactam antibiotics were the most commonly prescribed (37.6%), followed by fluoroquinolones (26.26%) and macrolides (13.45%). But performing culture sensitivity tests were rather uncommon (3.8%, n = 101). For multiple infections, beta-lactam antibiotics (such as amoxicillin and cefuroxime) were the most commonly prescribed antibiotics (2.26%, n = 60), followed by macrolides (such as azithromycin and Clindamycin) and fluoroquinolones (eg, ciprofloxacin and levofloxacin).Conclusion: Respiratory tract infections are the most prevalent infectious disease among hospital patients, who are primarily in their 20s. The frequency of performing culture tests is low. Therefore, it is important to promote culture sensitivity testing in order to support the prudent use of antibiotics. Guidelines for anti-microbial stewardship programs are also highly recommended.Keywords: antibiotics, infections, prescribing pattern, Hail region, Saudi Arabia